2016
DOI: 10.2106/jbjs.o.00407
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Mesenchymal Stem Cells to Autologous Platelet-Enhanced Fibrin Scaffolds in Chondral Defects

Abstract: APEF supported repair of critical-size full-thickness chondral defects in horses, which was not improved by the addition of BMDMSCs. This work supports further investigation to determine whether APEF enhances cartilage repair in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 50 publications
1
64
0
Order By: Relevance
“…29 When MSCs were instead combined with platelet-enhanced fibrin scaffolds in a lateral trochlear ridge defect of the stifle joint, ectopic bone formed in the repair tissue, which resulted in a thinner repair tissue when compared with cell-free scaffolds alone. 44 These findings indicated that MSCs should not be combined with platelet-enhanced fibrin scaffold for cartilage regeneration owing to the risk of bone formation. 44 In contrast, when autologous, culture-expanded chondroprogenitor cells were implanted in fibrin scaffolds, improved cartilage repair tissue was observed when compared with culture-expanded allogeneic chondroprogenitor cells or fibrin scaffold alone.…”
Section: Equine Models Of Focal Cartilage Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…29 When MSCs were instead combined with platelet-enhanced fibrin scaffolds in a lateral trochlear ridge defect of the stifle joint, ectopic bone formed in the repair tissue, which resulted in a thinner repair tissue when compared with cell-free scaffolds alone. 44 These findings indicated that MSCs should not be combined with platelet-enhanced fibrin scaffold for cartilage regeneration owing to the risk of bone formation. 44 In contrast, when autologous, culture-expanded chondroprogenitor cells were implanted in fibrin scaffolds, improved cartilage repair tissue was observed when compared with culture-expanded allogeneic chondroprogenitor cells or fibrin scaffold alone.…”
Section: Equine Models Of Focal Cartilage Healingmentioning
confidence: 99%
“…44 These findings indicated that MSCs should not be combined with platelet-enhanced fibrin scaffold for cartilage regeneration owing to the risk of bone formation. 44 In contrast, when autologous, culture-expanded chondroprogenitor cells were implanted in fibrin scaffolds, improved cartilage repair tissue was observed when compared with culture-expanded allogeneic chondroprogenitor cells or fibrin scaffold alone. 45 Although, chondroprogenitor cells may differ significantly from MSCs, the study suggests further investigation into using cells within a scaffold.…”
Section: Equine Models Of Focal Cartilage Healingmentioning
confidence: 99%
“…Most of these studies suggest promising results with improved cartilage regeneration between 3 months and 2 years. 26,[32][33][34][35][36] Significant superior histologic evidence of cartilage regeneration when using hydrogels are reported when compared to empty defects. The cell sources, collection techniques, cell processing, qualitative and quantitative characterizations, and delivery methods vary widely between studies.…”
Section: Preclinical Animal Modelsmentioning
confidence: 99%
“…In general the implantation of undifferentiated MSCs has been shown to promote the accumulation of cartilage‐like repair tissue, although this approach does not reliably result in regeneration of articular cartilage . Further, several animal studies have reported cartilage healing with undifferentiated MSC grafts that was no better than acellular controls . Therefore, controlled induction of chondrogenesis appears to be an important aspect of the use of MSCs for cartilage tissue engineering.…”
mentioning
confidence: 99%
“…1 Further, several animal studies have reported cartilage healing with undifferentiated MSC grafts that was no better than acellular controls. [2][3][4] Therefore, controlled induction of chondrogenesis appears to be an important aspect of the use of MSCs for cartilage tissue engineering.…”
mentioning
confidence: 99%